EKSISTENSI MINORITAS MUSLIM TOBA DI KOTA BALIGE - Fitriyani, Indah; Irwansyah, Irwansyah; Jailani, Muhammad (CV. Kalimasada Group, 2024)
This study discusses the existence of the Toba Muslim Minority in Balige City. Basically, the existence of society is one form of creating a set of components in an area. Similarly, every component of society will adjust to the surrounding environment. The potential for the formation of a typology of people in Balige City is grouped based on the religion adhered to. In general, the majority group is embraced by the Christian community while the minority group is embraced by the Muslim community. This research uses 2 theories reviewed from sociology and social philosophy. in the sociological review, this research is studied with Parsons' theory and its AGIL scheme, while in the review of social philosophy, this research uses Will Kymlicka's minority rights theory. This research uses qualitative methods with the type of field research (field research). Data collection techniques such as observation, interviews, and documentation. The result of this study is the existence of the Toba Muslim minority in Balige City into an interpretation of Islam in Batak Toba. The existence of Islam in Balige City can survive so far so that it has experienced developments such as the increasing number of worshippers. This will require improving the facilities of houses of worship for Muslims in worship. The government of the Ministry of Religious Affairs of Balige City tried to overcome this by facilitating the establishment of mosques and arranging the certification of the status of the land to avoid land disputes. Similarly, the views of the majority community towards minority communities are still relatively good. However, there are still obstacles found in interacting such as there are still some minority communities who have not been able to socialize. So they hope that minorities can blend into the majority society with each other. The conclusion of the study is that Islam can maintain its existence and is well accepted in Balige City. However, limitations as a minority community does not close will cause its slowness in developing. Such as facilities for houses of worship that have not been fulfilled adequately and so on.